2018
DOI: 10.1038/s41525-018-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

New insights into structural features and optimal detection of circulating tumor DNA determined by single-strand DNA analysis

Abstract: Circulating cell-free DNA (cfDNA) has received increasing interest as an apparent breakthrough approach in diagnostics, personalized medicine, and tumor biology. However, the structural features of cfDNA are poorly characterized. Specifically, the literature has discrepancies with regards to cfDNA size profile. We performed a blinded study of the distribution of cfDNA fragment sizes in cancer patient plasma (n = 11), by various ultra-deep-sequencing approaches and quantitative PCR (Q-PCR). Whole-genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 41 publications
(98 reference statements)
4
106
0
1
Order By: Relevance
“…It may also increase following intense effort. We (Sanchez et al, 2018) and others (Jiang et al, 2017;Underhill et al, 2018) revealed that cirDNA size profile shows a characteristic nucleosome fragmentation pattern. Our recent observations revealed that high molecular weight cirDNA fraction in the plasma of healthy individuals is minor, and corresponds to approximatively 12% of the total cirDNA fragment number (unpublished data).…”
Section: Nuclear Dnasupporting
confidence: 55%
“…It may also increase following intense effort. We (Sanchez et al, 2018) and others (Jiang et al, 2017;Underhill et al, 2018) revealed that cirDNA size profile shows a characteristic nucleosome fragmentation pattern. Our recent observations revealed that high molecular weight cirDNA fraction in the plasma of healthy individuals is minor, and corresponds to approximatively 12% of the total cirDNA fragment number (unpublished data).…”
Section: Nuclear Dnasupporting
confidence: 55%
“…These methods can also eliminate the need for biopsy, additionally providing mutation-related information that allows easy monitoring of the tumor and provides therapeutic potential [209]. Furthermore, cfDNAs contain information on the mutations that affect treatment, facilitate individualized therapeutic examining, and non-invasive follow-up that may enable better cancer management [210]. However, the extraction and amplification of cfDNA can be demanding due to high DNA fragmentation and low concentration in the bloodstream [211].…”
Section: Circulating Free Dnamentioning
confidence: 99%
“…In contrast, NcfDNA had a more homogenous distribution, conventionally peaking at 167 bp, corresponding to mono-nucleosomes ( Figure 1D). 17,28 Paired-end sequencing enables high-resolution measurement of DNA size but has a practical upper limit of readout at ~1000 bp. Since no McfDNA was detected between 500 bp and 1000 bp, Whole Genome Sequencing only detected the minor fraction formerly revealed by gel electrophoresis ( Figure 1C).…”
Section: Mitochondrial Cell-free Dna Size Distribution and Stabilitymentioning
confidence: 99%
“…In addition, the structure of McfDNA is currently unknown. In contrast, the structure of circulating DNA of nuclear origin is being characterized and mono and di‐ nucleosomes and, to a lesser extent, transcription factors are found as stabilized cell‐free DNA (cfDNA)‐associated structures in the blood‐stream . It is expected that there are important configuration differences between nuclear and mitochondrial circulating DNA, since mitochondrial DNA is a small circular genome, without protective histones, and thus is more sensitive to degradation in the circulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation